Asymptotic representations of solutions of nonautonomous ordinary differential equations: Asymptotic representations of solutions - Evtukhov, V. M.; Droggina, A. V.; Евтухов, В. М.; Дрожжина, А.В.; Євтухов, В. М.; Дрожжина, А. В. (Institute of Mathematics, NAS of Ukraine, 2019)
The conditions of existence and asymptotic representations as $t\uparrowω \ (ω\le +∞)$ are obtained for one class of solutions of nonautonomous differential equations of the $n$th order that are asymptotically close, in a certain sense, to the equations with regularly varying nonlinearities.